The Effect of a Company's Financial Performance on a Company's Value - Siregar, Firman; Achsani, Noer Azam; Bandono, Bayu (International Journal Labs, 2023)
An investor evaluates a company's success by analyzing its low valuation. Investors hold the expectation that a firm would enhance its performance in the early years subsequent to an initial public offering (IPO) as a means to evaluate its future potential. Consequently, there is a widely held belief that the success of a firm has an impact on its overall value. The COVID-19 pandemic that occurred from 2020 to 2021 represents a remarkable occurrence that might potentially influence both the performance and value of a firm. The focus of this study is the firm that had an Initial Public Offering (IPO) in 2019, consisting of 31 companies. The financial report data analyzed in this study pertains to the years 2019-2021. The study used panel data regression analysis to examine the relationship between corporate value dependent variables (Tobin's Q), corporate performance independent factors (ROA, ROE, DAR, DER, CR, TATO, GR), and COVID-19 dummy variables. The valuation of the firm is concurrently and substantially affected by all of the independent factors as well as a binary variable. The primary determinant that exerts substantial downward pressure on the company's valuation is the COVID-19 pandemic, as investors exhibit considerable uncertainty over its potential financial and operational ramifications. The adjusted R2 values obtained are 0.730134 and 0.540228. This finding indicates that the relationship between corporate performance and the impact of COVID-19 on corporate value (measured by Tobin's Q) accounts for 73.01% of the observed variation, while the remaining 26.99% may be attributed to other factors.